2022
DOI: 10.3390/vaccines10081198
|View full text |Cite
|
Sign up to set email alerts
|

Overview of Tools and Measures Investigating Vaccine Hesitancy in a Ten Year Period: A Scoping Review

Abstract: The challenge of vaccine hesitancy, a growing global concern in the last decade, has been aggravated by the COVID-19 pandemic. The need for monitoring vaccine sentiments and early detection of vaccine hesitancy in a population recommended by the WHO calls for the availability of contextually relevant tools and measures. This scoping review covers a ten year-period from 2010–2019 which included the first nine years of the decade of vaccines and aims to give a broad overview of tools and measures, and present a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 73 publications
0
17
0
Order By: Relevance
“…In a scoping review of validated tools to measure vaccine hesitancy from 2010 to 2019, the authors found 26 articles that mostly focused on parent perceptions of routine childhood immunizations and none on validating tools among HCWs. 21 The studies presented in our systematic review help to fill the gap between the validated tools on HCW vaccine confidence. 21 , 41 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a scoping review of validated tools to measure vaccine hesitancy from 2010 to 2019, the authors found 26 articles that mostly focused on parent perceptions of routine childhood immunizations and none on validating tools among HCWs. 21 The studies presented in our systematic review help to fill the gap between the validated tools on HCW vaccine confidence. 21 , 41 …”
Section: Discussionmentioning
confidence: 99%
“… 21 The studies presented in our systematic review help to fill the gap between the validated tools on HCW vaccine confidence. 21 , 41 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several topics were addressed in the Special Issue “New Insights in Vaccination and Public Health” in its first year of publication. Many of these explored the phenomenon of vaccine hesitancy [ 17 , 20 , 23 , 25 , 26 , 27 , 28 , 30 , 31 , 32 ] and, in particular, the acceptability of the COVID-19 vaccine [ 17 , 25 , 26 , 30 , 31 ] and the anti-influenza vaccine [ 23 , 28 , 33 ]. The role of ICTs was examined in relation to their influence on health choices [ 21 , 23 , 30 ] and in relation to the use of new technologies in the field of vaccinology [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Vaccination is one of the most effective strategies against infectious diseases (Jordan et al, 2022;Oduwole et al, 2022). The success of the PRV eradication campaign is mainly attributed to the application of the excellent PRV vaccine (McFerran and Dow, 1970;Sun et al, 2016;Freuling et al, 2017).…”
Section: Live Prv Vaccinementioning
confidence: 99%